Diagnosis and Management of Choledochal Cyst : A Single Center Experience - Malla, Bala Ram; Shakya, Yagya Ratna; Rajbhandari, Nripesh (Journal of Nepalgunj Medical College, 2019)
Objective: Choledochal cyst is cystic dilatation of intrahepatic and/ or extrahepatic bile duct. Its incidence is 1 in 1000 in Asian population. The objective of the study was to study the presentation, diagnosis, treatment and postoperative outcome of choledochal cyst operated in Dhulikhel Hospital, Kathmandu University Hospital, Dhulikhel, Nepal. Methods: This retrospective study was done by reviewing all the records of patients with choledochal cyst who underwent operative treatment in Dhulikhel Hospital from January 2015 to July 2019. Results: We analyzed twenty cases of Choledochal cyst. It was found to be common in age group (21-30 ) years with female preponderance (85%). Most common presenting symptom was abdominal pain. Abdominal Ultrasonography was the initial diagnostic tool. Todani type I choledochal cyst was the commonest type. All the cases underwent complete excision of extrahepatic biliary tree followed by hepato-jejunostomy. There was no post-operative anastomosis stricture in follow up period. Conclusion: Choledochal cyst presents commonly with abdominal pain. It can be diagnosed with abdominal ultrasonography. It has good outcome if treated adequately with good surgical technique.